Herpesvirus telomerase RNA (vTR) with a mutated template sequence abrogates herpesvirus-induced lymphomagenesis. - Benedikt B Kaufer; Sina Arndt; Sascha Trapp; Nikolaus Osterrieder; Keith W Jarosinski (PLoS Pathogens, 2011)
Telomerase reverse transcriptase (TERT) and telomerase RNA (TR) represent the enzymatically active components of telomerase. In the complex, TR provides the template for the addition of telomeric repeats to telomeres, a protective structure at the end of linear chromosomes. Human TR with a mutation in the template region has been previously shown to inhibit proliferation of cancer cells in vitro. In this report, we examined the effects of a mutation in the template of a virus encoded TR (vTR) on herpesvirus-induced tumorigenesis in vivo. For this purpose, we used the oncogenic avian herpesvirus Marek's disease virus (MDV) as a natural virus-host model for lymphomagenesis. We generated recombinant MDV in which the vTR template sequence was mutated from AATCCCAATC to ATATATATAT (vAU5) by two-step Red-mediated mutagenesis. Recombinant viruses harboring the template mutation replicated with kinetics comparable to parental and revertant viruses in vitro. However, mutation of the vTR template sequence completely abrogated virus-induced tumor formation in vivo, although the virus was able to undergo low-level lytic replication. To confirm that the absence of tumors was dependent on the presence of mutant vTR in the telomerase complex, a second mutation was introduced in vAU5 that targeted the P6.1 stem loop, a conserved region essential for vTR-TERT interaction. Absence of vTR-AU5 from the telomerase complex restored virus-induced lymphoma formation. To test if the attenuated vAU5 could be used as an effective vaccine against MDV, we performed vaccination-challenge studies and determined that vaccination with vAU5 completely protected chickens from lethal challenge with highly virulent MDV. Taken together, our results demonstrate 1) that mutation of the vTR template sequence can completely abrogate virus-induced tumorigenesis, likely by the inhibition of cancer cell proliferation, and 2) that this strategy could be used to generate novel vaccine candidates against virus-induced lymphoma.